Quill mites (Acari: Prostigmata: Syringophilidae) from African passeriform birds - Skoracki, Maciej; Sikora, Bozena (Zootaxa, 2003)
Two new species of quill mites (Acari: Prostigmata: Syringophilidae) collected from passeriform birds from Africa are described and illustrated: Aulobia cisticolae sp. n. from the Red-faced Cisticola Cisticola erythrops (Hartlaub, 1857), the Singing Cisticola C. cantans (Heuglin, 1869) and the Whistling Cisticola C. lateralis (Fraser, 1843) (Sylviidae) and Syringophilopsis corvinae sp. n. from the Yellow-billed Shrike Corvinella corvina (Shaw, 1809) (Laniidae). Two new host species of the family Syrinophilidae are given.